WEBSITE-BASED INVENTORY APPLICATION USING EXTREME PROGRAMMING METHOD AT SINAR JAYA MOTOR COMPANY - Malvin Adrianus; Honni Po (Universitas Teknokrat Indonesia, 2023)
Sinar Jaya Motor Company is a company engaged in the provision of car and truck spare parts services based in Jakarta. In the activities of processing warehouse goods data, incoming goods data, outgoing goods data, factory return data, order return data, order data, the process of making reports for business processes with these data is still done manually, causing problems, namely inaccuracy of goods data due to process data entry is still long, prone to errors and report generation takes quite a long time because you have to do a document search first. The research objective is to produce a website-based inventory application that can solve problems at the Sinar Jaya Motor company. Data collection methods in this study were literature study, interview methods, and observation, while the system design method used was Extreme Programming which consisted of planning, designing, coding, and testing stages. In its design, the researcher adopts a structured programming paradigm and is written using the HTML, CSS, PHP, Javascript and MySQL database programming languages. The author will also use the Boostrap5 framework to produce an attractive and responsive website appearance. It is hoped that the existence of a website-based web inventory which is the result of this research can be used for data entry of warehouse goods, incoming goods data, outgoing goods data, factory return data, order return data, order data so as to produce reports for all business processes within the company, storage and document printing. The conclusion of this study is that the website-based inventory application for transporting goods that has been built can help solve the problems experienced by the Sinar Jaya Motor company in managing goods data and other data and make it easier for this company's employees to make and print documents and monthly reports so as to facilitate the process ongoing business.